Memória, cultura popular e enraizamento. Uma análise dos costumes e práticas culturais dos bairros do Roger e Tambiá em João Pessoa PB. - Nascimento, Mayk Andreele do (2010)
This paper explores the manifestations of popular culture in neighborhoods of Roger and also in the city of Joao Pessoa, in a period between 1900 and 1960 decades. The aim of this study was to understand the transformations occurring in the context of popular culture in the region, emphasizing the field of power relations that is located on the popular culture of the hegemonic culture. During the twentieth century, many changes occurred in the city of Joao Pessoa, especially with regard to its urban setting, working conditions, housing and the broader cultural context. These changes, in turn, caused changes in the customs and cultural practices popular in the region comprising the districts of Roger and Tambiá. The aim of this study is to examine the customs and cultural practices popular in this transformation process. In this sense, my concern is with cultural processes and the experiences of its participants. Therefore, the memory of local residents is crucial to this research. It is this memory that guides us in the ways of popular culture as it is from there that we can take account of the meanings of culture.